Making Good People Rather than Making People Good? - Platten, Stephen (Journal of Anglican studies, 2015)
The paper investigates the roots of a virtue-based ethics within Anglicanism starting with the Caroline tradition in the seventeenth century. In the twentieth century there was a rebirth of Anglican Moral Theology' with the work of Kenneth Kirk, Robert Mortimer and Lindsay Dewar. Issues of perfectibility are examined. The recovery of the Orthodox tradition of deification at the present time and the rebirth of virtue ethics through the work of Alasdair McIntyre are explored. Anglicanism is rooted in an approach where grace is already present in the natural order but which is enhanced by an integralist approach to theology bringing together doctrinal, ascetic and moral theology in one compass.